2017
DOI: 10.1155/2017/4670231
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Customer Quality of Experience System for a Cellular Network

Abstract: Improving customer-perceived service quality is a critical mission of telecommunication service providers. Using 35 billion call records, we develop a call quality score model to predict customer complaint calls. The score model consists of two components: service quality score and connectivity score models. It also incorporates human psychological impacts such as the peak and end effects. We implement a large-sized data processing system that manages real-time service logs to generate quality scores at the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Packet length allocation is: Where the likelihood of a non-segmented message packet is that a packet has a continuous length and a possibility its packet belongs to segments and a distance lower than that of a packet. The probability is [4]   ( )  …”
Section: Iii30 Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Packet length allocation is: Where the likelihood of a non-segmented message packet is that a packet has a continuous length and a possibility its packet belongs to segments and a distance lower than that of a packet. The probability is [4]   ( )  …”
Section: Iii30 Methodologymentioning
confidence: 99%
“…In this job, the techniques were not addressed only the outcomes were shown graphically. [4][5] The objective of carrying out this research was to evaluate the voice quality in Long Tern Evolution (LTE) through the use of various codec mode set. This study has shown that all mode sets worked in the same manner under distinct circumstances of track loss.…”
Section: Iireview Of Related Workmentioning
confidence: 99%
“…From the results of the clustering analysis, the features/variables/attributes that significantly explain the label can be identified. Rejection of features/variables/attributes can be done based on explanatory power considering the multicollinearity between the features/variables/attributes and explanation rate of each feature/variable/attribute (Jung et al, 2017). LDA method finds the projection hyperplane that minimizes the interclass variance and maximizes the distance between the projected means of the classes (Xanthopoulos et al, 2013).…”
Section: Analyzing and Synthesizing Datamentioning
confidence: 99%